(Neoclassical) rhetorical analysis of George A. Kennedy in the media science perspective - Worsowicz, Monika (Methods of communication and media researches. Theoretical and analytical perspective, 2021)
The chapter describes the method of rhetorical analysis by George A. Kennedy and its modification to meet the needs of media analysis. It includes a discussion of the objectives and subject of research as well as methods of analysis, taking into account the possibilities and limitations that the tool created for the needs of biblical exegesis puts on the researcher of the content of contemporary media. The proposed approach can also be used by students when writing bachelor's and master's theses.